Reduced-order fractional descriptor observers for a class of fractional descriptor continuous-time nonlinear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Fractional descriptor reduced-order nonlinear observers for a class of fractional descriptor continuous-time nonlinear systems are proposed. Sufficient conditions for the existence of the observers are established. The design procedure for the observers is given and demonstrated on a numerical example.
Keywords: fractional systems; descriptor systems; nonlinear systems; reduced-order observer